Democracy Deficit in China: A Choice or Foreordained - Wijaya, Trissia (Jurnal Ilmiah HUBUNGAN INTERNASIONAL, 2015)
This paper attempts to analyze both internal and external determinants which influence the persistence of the democracy deficit in China, as Beijing successfully surpressed its peoples demand for democrartic change and freedom. This paper also examines how the longevity of one-party regimes has simply made democracy such a forgettable discourse. Meanwhile, this paper argues three watersheds of undemocratized China. First, the historical precedence has shown that attempts of electoral democracy have not been successful in China. Second, there is an absence of constructive engagement toward China by external powers, such as the European Union and the United States (henceafter, "US"). Third, democracy lacks strong support from large sections of Chinese society. This paper also sees the another perspective of how the monopolized power of Chinese Communist Party (henceafter, "CCP") has been substituting the implementation of liberal democracy through the meritrocacy system and creatingthe dependencies of middle class to government.